Signal‐to‐noise ratio penalties from a loss of stimulated echoes when using slab‐selective excitation in three‐dimensional fast spin echo imaging with long echo trains. (29th December 2022) - Snyder, Jeff; Seres, Peter; Wilman, Alan H.
Abstract: Three‐dimensional fast spin echo imaging with long echo trains combines high resolution with reasonable acquisition times and reduced specific absorption rate due to low refocusing flip angles. Typically, an entire volume is encoded (nonselective excitation) or localization can be performed with slab select excitation, which uses a long 90° pulse for precise localization, followed by a preliminary nonselective 180° pulse bounded by spoiler gradients to destroy signal outside of the volume of interest. Subsequent flip angles in the train are nonselective and identical between the two methods. The inclusion of the initial selective pulse and spoiler gradients results in a signal‐to‐noise ratio (SNR) penalty for slab selection, beyond the slice‐averaging dependence, arising from a loss of stimulated echoes. SNR differences are explored using Bloch equation simulations of a T2‐weighted 96 echo train sequence with varying parameters including T2, T1, and B1 + and compared with phantom and in vivo brain, neck, and knee experiments. In vivo SNR measurements in the three regions showed a maximum decrease of selective SNR by 29% (gastrocnemius muscle), 25% (pons), and 22% (globus pallidus), despite similar experimental parameters to nonselective experiments. Decreased SNR was compounded by B1 + variation affecting prescribed flip angles with further smaller reductions with T2 and T1 times. In conclusion, the elimination of coherences via the preliminary nominal 180° pulse and spoiler gradients in addition to the extended echo timing from the long excitation pulse resulted in a reduction in SNR compared with the nonselective case. Consideration of the required SNR and chosen anatomy as well as sequence restrictions should be weighed before choosing slab‐selective excitation. Abstract : SNR differences between slab selective and nonselective excitation in 3D FSE with long echo trains were compared in brain, neck and knee experiments. A maximum SNR decrease with slab excitation was observed in the three regions of 29% (gastrocnemius muscle), 25% (pons) and 22% (globus pallidus), despite similar parameters to nonselective experiments. This reduction is due to increased T2 decay and coherence elimination by slab selective excitation, and therefore, the excitation method should be weighed based on anatomy and SNR.